VD_FINDINFO Décision / 2019 / 166 vom 6. Mai 2019 - VD Tribunal cantonal (2019)
NON-LIEU, ESCROQUERIE, ABUS DE CONFIANCE, APPROPRIATION ILLÉGITIME, GAGE | 137 CP, 138 ch. 1 CP, 146 al. 1 CP, 310 CPP (CH)